2007
DOI: 10.1111/j.1551-2916.2007.01884.x
|View full text |Cite
|
Sign up to set email alerts
|

Alumina/Zirconia Micro/Nanocomposites: A New Material for Biomedical Applications With Superior Sliding Wear Resistance

Abstract: In the present investigation, the sliding wear behavior is described for Al 2 O 3 /ZrO 2 micro/nanocomposites and monolithic alumina of similar grain size under defined conditions of a constant sliding speed and different loads (20-150 N). Nano ZrO 2 particles (1.7 vol%) were observed uniformly distributing throughout the composites, and most of them were located within the matrix alumina grains. The wear rate of the alumina and the micro/nanocomposites increased as the contact load increased and a clear trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 52 publications
0
22
0
1
Order By: Relevance
“…Here the concept of tailoring strength by inhibition of crack initiation makes use of the heterogeneous thermoelastic properties of the micro-nano hybrid composite phases. Due to thermal expansion misfit, the ceramic matrix is set under compressive residual stresses [39]. Therefore, the critical applied tensile stress for crack initiation is shifted to a higher level.…”
Section: Discussionmentioning
confidence: 99%
“…Here the concept of tailoring strength by inhibition of crack initiation makes use of the heterogeneous thermoelastic properties of the micro-nano hybrid composite phases. Due to thermal expansion misfit, the ceramic matrix is set under compressive residual stresses [39]. Therefore, the critical applied tensile stress for crack initiation is shifted to a higher level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the addition of small quantities of alumina to zirconia leads to aid densification and reduction in grain growth during the sintering [5,6,9,14,17,18]. Accordingly, a facile synthetic method for large scale production of ultra fine particles of zirconia and zirconia solid solutions namely alumina doped zirconia is absent.…”
Section: Introductionmentioning
confidence: 96%
“…For instance, they have been used in the fields of solid oxide fuel cells, oxygen sensors, electro-optical materials, catalysts, high performance transformation-toughened structural engineering ceramics and bioceramics, etc. [1][2][3][4][5][6][7]. Accordingly, great efforts have been expended in the synthesis approaches of the material with controlling the size and shape of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…Also in alumina/zirconia micro/nanocomposites for biomedical applications Bartolomé et al. determined residual strain and stress distributions to gain a higher understanding of the materials wear mechanisms [13]. Gibmeier et al reported that in indentation tests microhardness is highly affected by residual stresses [14].…”
Section: Introductionmentioning
confidence: 99%